La biodanza como estrategia psicoeducativa para disminuir conductas agresivas en estudiantes de octavo año paralelo a, de la unidad educativa Pio Jaramillo Alvarado, 2018-2019. - Cabrera Toledo, Judith Patricia (2020)
Aggressive behaviors in students are one of the most common problems in the school context, they cause physical and psychological damage, which hinders interpersonal relationships and harmony within the classroom; For this reason, the present investigation called: BIODANCE AS A PSYCHOEDUCATIONAL STRATEGY TO REDUCE AGGRESSIVE BEHAVIORS IN EIGHTH YEAR STUDENTS, PARALLEL A, FROM THE EDUCATIONAL UNIT PIO JARAMILLO ALVARADO 2018,2019; Its general objective is "To implement biodanza as a psychoeducational strategy to reduce aggressive behaviors in eighth year parallel A students." It was a quantitative, descriptive, cross-sectional study with a quasi-experimental design. The methods used were; analytical, synthetic, inductive, deductive, and statistical. In addition, the Buss and Perry AQ Aggression Questionnaire was used, applied to a sample of 27 eighth-year students. The results obtained when applying the aforementioned test resulted in the levels of hostility and verbal aggressiveness concurring in a higher percentage in the school environment. The present study is concluded indicating that, after the implementation of biodanza as a psychoeducational strategy, significant attitudinal changes were evidenced in the students, due to which the levels of aggressiveness decreased satisfactorily, thus generating a warm study environment based on respect and the tolerance.